Shape and rate of movement of the invasion front of Xylella fastidiosa spp. pauca in Puglia - Kottelenberg, David; Hemerik, Lia; Saponari, Maria; van der Werf, Wopke (Scientific reports, 2021)
In 2013, Xylella fastidiosa spp. pauca was first reported in Puglia, Italy, causing the olive quick decline syndrome (OQDS). Since then the disease has spread, prompting the initiation of management measures to contain the outbreak. Estimates of the shape of the disease front and the rate of area expansion are needed to inform management, e.g. the delineation of buffer zones. However, empirical estimates of the invasion front and the rate of spread of OQDS are not available. Here, we analysed the hundreds of thousands of records of monitoring data on disease occurrence in Puglia to estimate the shape of the invasion front and the rate of movement of the front. The robustness of estimation was checked using simulation. The shape of the front was best fitted by a logistic function while using a beta-binomial error distribution to model variability around the expected proportion of infected trees. The estimated rate of movement of the front was 10.0 km per year (95% confidence interval: 7.5–12.5 km per year). This rate of movement is at the upper limit of previous expert judgements. The shape of the front was flatter than expected. The fitted model indicates that the disease spread started approximately in 2008. This analysis underpins projections of further disease spread and the need for preparedness in areas that are still disease free.